Antithrombotic regimens for the prevention of major adverse cardiac events in chronic coronary syndrome: A systematic review and network meta-analysis - Marques, Gustavo Lenci; Albuquerque, Arthur Mendonça; Romaniello, Gabriela; Bozzi, Fernanda Proença Lepca; da Cunha, Gustavo Pereira; Andraus, Gabriel Savogin; Hastreiter, Gabriel; Maniesi, Barbara; Baena, Cristina; Guedes, Murilo (Frontiers in Cardiovascular Medicine, 2023)
Backgroud: Antithrombotic therapy is the cornerstone of chronic coronary syndrome (CCS) management. However, the best treatment option that optimally balances bleeding risk and efficacy remains undefined. Our objective was to evaluate the effectiveness and safety of antithrombotic options and identify the optimal treatment option for patients with CCS. Methods: We used the MEDLINE, CENTRAL and Embase databases to search for randomized controlled trials with follow-up periods longer than 12 months that compared aspirin (ASA) monotherapy with other antithrombotic therapies in patients with CCS. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used. Extracted data (hazard ratios [HR]) were pooled using Bayesian fixed-effect models, allowing the estimation of credible intervals (CrI) and posterior probabilities of benefit, harm, and practical equivalence. Confidence in the results was assessed with the Confidence In Network Meta‐Analysis (CINeMA) tool. The primary efficacy and safety outcomes were major adverse cardiovascular events (MACE) and primary bleeding, respectively. Secondary outcomes were acute myocardial infarction, ischemic stroke, all-cause, and cardiovascular-specific mortality. Results: Five trials with a total of 80,605 patients were included. Mean patient age ranged from 61 to 69 years, while 20.3% to 31.4% were women. The reference treatment was ASA monotherapy. ASA + prasugrel 10 mg and clopidogrel 75 mg monotherapy presented the greatest benefit for MACE (HR 0.52 [95% CrI, 0.39 – 0.71]; and 0.68 [95% CrI, 0.54 – 0.88]). There was a probability of 98.8% that ASA + ticagrelor was practically equivalent to ASA monotherapy. Regarding the primary bleeding outcome, clopidogrel 75 mg monotherapy performed best (HR 0.64 [0.42, 0.99]). There was a probability of 97.4% that ASA + Prasugrel 10mg increases bleeding (HR>1.0). Secondary outcome results followed a similar treatment ranking pattern as in primary outcomes. Overall, CINeMA confidence ratings were judged as either low or very low. Conclusions: These results revealed that clopidogrel monotherapy might provide the best risk-benefit balance in treating CCS. However, low confidence ratings hamper definite conclusions. Our analysis suggests revising guidelines currently recommending ASA monotherapy for patients with CCS.